2007
DOI: 10.1007/s10327-007-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate, a major tea catechin, induces biofilm formation of Pseudomonas syringae pv. theae

Abstract: Plants constitutively produce a variety of secondary metabolites that have antimicrobial activities against phytopathogens; however, interactions between these performed antimicrobial compounds and phytopathogens were poorly understood. In this study, interactions between epigallocatechin gallate (EGCg), which was a major tea catechin that had antimicrobial activities against varieties of bacteria, and Pseudomonas syringae pv. theae (P.s. theae), the causal of bacterial shoot blight of tea, were investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Up to 4% of the dry mass of green tea is carbohydrate, and extracts were shown to promote biofilm formation by P. syringae pv. theae even at low sub-inhibitory concentrations of EGCG, probably via cyclic diguanylate signal transduction (Horie and Kobata, 2002; Tomihama et al, 2007). P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 4% of the dry mass of green tea is carbohydrate, and extracts were shown to promote biofilm formation by P. syringae pv. theae even at low sub-inhibitory concentrations of EGCG, probably via cyclic diguanylate signal transduction (Horie and Kobata, 2002; Tomihama et al, 2007). P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin gallate can induce P. syringae biofilm formation. 171 Another study reported the conflicting effects of extracts from Cinnamomum species. Those from C. cassia inhibited biofilm formation by the Gram-negative E. coli, while C. nardus and C. zeylanicum extracts improved their biofilm formation potential.…”
Section: Targeting Biofilmsmentioning
confidence: 99%
“…A subinhibitory concentration of the antibiotic tobramycin was also reported to induce biofilm formation by Pseudomonas aeruginosa, and there was speculation that biofilm formation was an adaptive response to antibiotics produced by other bacterial species in the ecological niche (Hoffman et al 2005). Similarly, we revealed that a subinhibitory concentration of epigallocatechin gallate (EGCg), a major catechin in leaves of tea, induced biofilm formation of P.s.theae, although EGCg had lower antimicrobial activity of P.s.theae (Tomihama et al 2007).…”
Section: Introductionmentioning
confidence: 72%
“…Srain K9301-6 was isolated from liquid KB medium cultured for 4 weeks. K9301-6, which forms a small and wrinkled colony, is positive for both EPS and cellulose production (Tomihama et al 2007). Bacteria were grown at 25°C in King's B medium containing 1% sucrose (KBS) unless otherwise stated.…”
Section: Introductionmentioning
confidence: 97%